2009
DOI: 10.1007/s10725-009-9436-2
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 regulates the abscisic acid-induced antioxidant response of maize to combined drought and heat stress

Abstract: We investigated the interaction between heat shock protein 70 (HSP70) and abscisic acid (ABA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 41 publications
2
84
1
3
Order By: Relevance
“…Therefore, the Hsp70 chaperones might play a broader role by participating in modulation of the expression of many downstream genes in signal transduction pathways (Nollen and Morimoto, 2002). Hu et al (2010) have suggested that HSP70 may play a crucial role in ABAinduced antioxidant defence of maize to the combination of drought and heat. Grigorova et al (2011) have observed an increase in Hsp70 in wheat plants under drought or heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Hsp70 chaperones might play a broader role by participating in modulation of the expression of many downstream genes in signal transduction pathways (Nollen and Morimoto, 2002). Hu et al (2010) have suggested that HSP70 may play a crucial role in ABAinduced antioxidant defence of maize to the combination of drought and heat. Grigorova et al (2011) have observed an increase in Hsp70 in wheat plants under drought or heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the induction of Hsps was higher in response to drought and heat shock compared with heat shock or drought individually [37]. In maize, Hsp70 and sHsps (sHsp17.2, sHsp17.4 and sHsp26) are responsive to a combination of drought and heat stress [12,38]. Four Hsp genes (Hsp17.8, Hsp26.3, Hsp70 and Hsp101b) in Triticum aestivum plants were monitored via one-step RT-PCR and SDS-PAGE analysis in plants subjected to water deprivation or high temperature individually and in combination.…”
Section: Function Of Oshsps Under Drought and Heat Stressmentioning
confidence: 99%
“…Hsp genes regulated by ABA have been reported in several plant species, such as maize, tobacco, wheat and rice [12,36,[42][43][44]. Results of studies with an ABA-deficient mutant indicated that endogenous ABA regulated Hsp70 synthesis in the leaves and roots of maize seedlings exposed to drought, heat, and combined drought and heat stress, which implied that ABA may improve plant tolerance to stress by increasing Hsp70 expression.…”
Section: Oshsp Genes May Be Involved In Aba-regulated Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis has shown that Hsp101 is absolutely essential for thermal tolerance in Arabidopsis (Tonsor et al 2008), and this Hsp has been reported to play a role in preventing oxidative stress (Zhang et al 2009). Hsp70 is one of the major classes of chaperone molecules and is involved in a variety of tasks in eukaryotic cells, and increased Hsp70 synthesis results in a marked increase in stress tolerance (Hu et al 2010;Montero-Barrientos et al 2010). Although plants generate an array of high molecular weight Hsps, most of the translation capacity is devoted to the synthesis of the small Hsps (e.g., Hsp15.7-CI and Hsp17.4-CIII) which also play an important role in the acquisition of thermal tolerance (Yildiz and Terzi 2008).…”
mentioning
confidence: 99%